The Views of Eastern Thinkers on Education and Upbringing - I. V. Xoldarova; R. I. Xomidova (Scientific Trends, 2025)
This article discusses the views of our Eastern thinkers and ancestors on education, upbringing, morality, and ethics in the process of educating primary school students. It also highlights pedagogical perspectives on the approaches, scientific research, and ideas related to education and upbringing expressed during the creative activities of Eastern thinkers, emphasizing the integration of moral education in imparting knowledge to the younger generation and its proper application in life.
Keywords: Education, upbringing, morality, ethics, perfect person, spirituality, ideal person, national values, national thinking, moral education.